(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
This article introduces the framework of Post-Normal Science (PNS) and identifies the types of policy questions to which it is most relevant. It then explores the role of public participation in research, with particular attention to citizen science. The discussion highlights its defining features, historical roots, and normative foundations that have guided its development, often building on pre-existing participatory practices. A concise case study in environmental health illustrates how collaboration between professionals and citizens can extend across the entire research process, demonstrating the value of knowledge co-creation in contexts characterized by uncertainty and divergent values.